Implementation of Shared Leadership in Elementary Schools in Decision Making - Saliya, Nurbaiti; Zebua, Ali Marzuki (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims to analyze the implementation of shared leadership in decision-making at SDN 94/III Kerinci, which is implemented to improve the quality of decision-making involving all school members. The subjects of the study consisted of the principal, teachers, and administrative staff at SDN 94/III Kerinci, located in Kerinci Regency, Jambi Province. The data collection techniques used were structured interviews and source triangulation to obtain valid and comprehensive data on the implementation of shared leadership. The collected data were then analyzed using descriptive qualitative data analysis methods. The results of the study indicate that SDN 94/III Kerinci consistently applies shared leadership in decision-making that is always adjusted to the school's vision and mission. Teachers and staff feel more appreciated and treated fairly when involved in the decision-making process, in contrast to the more authoritarian traditional leadership model. The interaction between the principal, teachers, and staff is also characterized by high respect, with equal opportunities to voice opinions. Despite challenges, such as differences of opinion among teachers and staff, the principal is able to manage this conflict wisely so that the decisions taken can reach a mutual agreement. Evaluation conducted after decision making also plays an important role in improving the quality and effectiveness of decisions. In conclusion, the implementation of shared leadership at SDN 94/III Kerinci has succeeded in improving the quality of decision making, building a sense of togetherness, and strengthening commitment and respect among all members of the school. This approach allows the school to achieve goals that are in line with the vision and mission that have been set together